Private risks and public dangers - Scott, Sue (Routledge library editions. British Sociological Association, 2018)
"Private Risk and Public Dangers is comprised of a collection of chapters which were originally papers presented in the 1991 British Sociological Association Conference on Health and Society, and they address a range of private risks and public dangers. Issues covered vary from the response to HIV and AIDS and 'foetal alcohol syndrome' to the nature of accidents. These seemingly diverse social situations within which emerges is that we need a more sociologically informed understanding of the personal shading the public dangers they are expected to manage."--